Local Wisdom in Agriculture of Urug Indigenous Village as an Alternative Biology Learning Resource - Lathifah, Suci Siti; Widodo, Ari; Kaniawati, Ida; Sriyati, Siti (KnE Social Sciences, 2024)
The purpose of this research is to identify and analyze local wisdom in the field of agriculture in Urug Traditional Village, which can be used as an alternative source of learning biology. This research was conducted from December 2021 to September 2022. This research is qualitative research with descriptive qualitative method. This research data collection technique included conducting observations, interviews, documentation studies, and product feasibility tests to several informants. The results show that local wisdom in the agricultural sector of Kampung Adat Urug can be used as a source for learning biology. The biology material in the local wisdom of the agricultural area of Kampung Adat Urug covers KD 3.1 and KD 4.1 topics related to biology, KD 3.2 and KD 4.2 topics related to biodiversity, and KD 3.11 and KD 4.11 topics related to ecosystems for grade 10 students. For grade 12 students, the material covers KD 3.1 and KD 4.1 topics related to growth and development. Future research should aim to develop teaching materials and learning media for biology based on the local wisdom of the Urug Traditional Village, combined with a diversified learning model. Keywords: urug indigenous village, local wisdom, biology learning resources